Dampak Pembangunan Infrastruktur Jalan Kendari – Toronipa Terhadap Pertumbuhan Ekonomi Masyarakat Kecamatan Soropia Kabupaten Konawe - Irma Irma; Irfan Ido; Jamal Harimudin; Weka Widayati; Anita Indriasary (JAGAT (Jurnal Geografi Aplikasi dan Teknologi), 2024)
The construction of the Kendari-Toronipa road in the Soropia District can have an impact on the economic growth of the community. This research aims to: (1) determine the distribution of community trade facilities along the Kendari-Toronipa Road before construction, during construction, and in operation (2018 - 2022); (2) assess the level of income difference in the community before construction and during operation (2018-2022). Data for this study were obtained through interviews with 91 respondents selected using random sampling method, and then analyzed using economic distribution analysis and paired sample t-test. The findings of this research indicate: (1) the number of economic facilities during construction was 93 units, during the construction phase was 140 units, and during operation was 186 units; (2) The results of the paired sample t test analysis show that before construction and construction which had an increase in income only occurred in Toronipa Village and Leppe Village, then income during construction and operations that received H0 were 8 villages, whereas at the time before construction and operation most of the villages received H0. in Soropia sub-district receive H0, which means there is a significant change in income.